5-Fluorouracil Management of Oculofacial Scars: A Systematic Literature Review. Issue 3 (May 2020) - Bui, Anh D.; Grob, Seanna R.; Tao, Jeremiah P.
Abstract : Purpose: To review the literature for the safety and efficacy of intralesional 5-fluorouracil (5-FU) in the management of oculofacial scars. Methods: A literature search was performed in July 2019 in the PubMed database to identify reports of the use of 5-FU injections for modulating oculofacial cutaneous scars. The search yielded 152 articles, of which 15 met criteria outlined for assessment. Data were abstracted from these 15 relevant articles. Results: While there were no high-level prospective randomized controlled trials, 8 were lower-quality randomized controlled trial, 3 were retrospective cohort studies, and 4 were case series. Most studies pooled results of facial and nonfacial cutaneous applications. Three studies focused solely on oculofacial applications, and these were all lower-level evidence studies. The study outcomes included scar dimension reduction, erythema, patient satisfaction score, observer assessment of scar improvement, and recurrence rates. 5-Fluorouracil was administered as monotherapy or as part of multimodality treatment with other agents (usually corticosteroids) or with CO2 laser, radiotherapy, or pulsed dye laser. 5-Fluorouracil was usually given as an intralesional injection, but in some studies, it was applied topically after micropuncture of the skin. The number and timing of treatments varied between studies. Overall, the level of safety of 5-FU was high. Pain with injection was the most common reported side effect. Other common adverse side effects included pruritus, telangiectasias, changes in pigmentation, and purpura, and 2 studies noted more serious events, such as ulceration, superficial necrosis, and local infection. There were no severe side effects such as anaphylaxis, immune suppression, secondary malignancy, systemic infection, blindness, or death. In all studies, 5-FU was associated with prophylaxis of oculofacial scars or improvement of keloids or hypertrophic scars in terms of reducing size, erythema, and pruritus. 5-Fluorouracil application was associated with favorable patient satisfaction and observer assessment scores especially compared with corticosteroid injections alone. Conclusions: High-quality randomized controlled trials are currently lacking, and the existing literature is predominately not specific to use of 5-FU on the face. These studies, however, suggest that intralesional 5-FU is safe and probably more effective than other options in the management of cutaneous scars in the oculofacial region. The delivery methods, timing, dosing, and concomitant therapies were highly variable. Further high-quality controlled studies specific to oculofacial scars may be indicated to assess the efficacy of 5-FU and to establish the best protocols for administering this medication. Abstract : The authors review the literature regarding the efficacy of intralesional 5-fluorouracil in the management of cutaneous oculofacial keloids and hypertrophic scars.Supplemental Digital Content is available in the text.